A simple model for the quench front propagation in a highly superheated particle bed. (June 2019) - Yeo, D.Y.; NO, H.C.
Highlights: Quenching rate can be predicted considering an equilibrium between hydraulic and thermal limits. It is important to consider thermal limit of quench front propagation for the prediction of quenching rate. The present model can predict the decreasing trend of heat flux along the bed temperature. Effect of particle size on heat removal rate is smaller than one expected from flooding-limit based models. Abstract: In this paper, a simple and fast-running model for the quenching of a particulate bed is suggested assuming two-step quenching: downward quench front propagation step and upward quench front propagation step. Most of the existing models are based on the assumption that the quenching rate is only hydraulically limited. However, the model suggested in this paper assumes that the quenching rate can be also thermally limited by the large thermal energy of a particulate bed in addition to the hydraulic limit of quenching. It turns out that the suggested model well predicted the decreasing trend of heat flux with increasing bed temperature. Also, it was found out that the effect of particle size on the heat removal during the quenching can be smaller than one expected from the flooding-limit based model. RMSE of the current model was 15% in comparison with 38% of Ginsberg's model.